Habitual physical activity improves outcomes among patients with myocardial infarction - Cai, Sidong; Huang, Fangmei; Wang, Run; Wu, Min; Liu, Mingya; Peng, Yufen; Cao, Gaozhen; Li, Yapin; Liu, Shuhong; Lu, Jiena; Su, Mengqi; Wei, Yinxia; et al. (Frontiers in Cardiovascular Medicine, 2023)
Purpose This study evaluates the association between habitual physical activity (HPA) and the outcomes of patients with myocardial infarction (MI). Methods Patients newly diagnosed with MI were divided into two groups based on whether they engaged in HPA, defined as an aerobic activity with a duration of no less than 150 min/week, before the index admission. The primary outcomes included major adverse cardiovascular events (MACEs), cardiovascular (CV) mortality, and cardiac readmission rate 1 year following the index date of admission. A binary logistic regression model was applied to analyze whether HPA was independently associated with 1-year MACEs, 1-year CV mortality, and 1-year cardiac readmission rate. Results Among the 1,266 patients (mean age 63.4 years, 72% male), 571 (45%) engaged in HPA, and 695 (55%) did not engage in HPA before MI. Patients who participated in HPA were independently associated with a lower Killip class upon admission (OR = 0.48: 95% CI, 0.32–0.71, p < 0.001) and a lower prevalence of 1-year MACEs (OR = 0.74: 95% CI, 0.56–0.98, p = 0.038) and 1-year CV mortality (OR = 0.50: 95% CI, 0.28–0.88, p = 0.017) than those who did not participate in HPA. HPA was not associated with cardiac-related readmission (OR = 0.87: 95% CI, 0.64–1.17, p = 0.35). Conclusions HPA before MI was independently associated with a lower Killip class upon admission, 1-year MACEs, and 1-year CV mortality rate.